Urolithin A in Central Nervous System Disorders: Therapeutic Applications and Challenges - Qiang Zhang; Wan Zhang; Xinya Yuan; Xiaohong Peng; Guangyuan Hu (Biomedicines)
With the global trend of population aging becoming increasingly pronounced, the incidence of central nervous system (CNS) disorders continues to rise, posing a significant challenge to public health systems worldwide. Currently, many CNS disorders lack effective treatments, prompting researchers to investigate the therapeutic potential of natural compounds. Urolithin A (UA), a gut microbiota-derived metabolite of ellagitannins and ellagic acid, can cross the blood–brain barrier and exhibits a favorable safety profile. This review summarizes the biosynthesis, pharmacokinetic profile, and key biological effects of UA, including its promotion of mitophagy and mitochondrial homeostasis, as well as its anti-inflammatory, antioxidant, anti-senescence, and anti-apoptotic properties. We comprehensively summarize the preclinical evidence demonstrating UA’s therapeutic potential in CNS disorders, such as Alzheimer’s disease, Parkinson’s disease, and stroke. Recent clinical trials involving UA are presented, followed by a thorough analysis of the challenges associated with translating UA-based interventions into clinical practice for CNS disorders. This work aims to support the development of UA-based therapies to improve patient outcomes and address the growing global burden of CNS disorders.